Analysis of Unconventional Oil and Gas Reservoirs using Well Logging, Geochemical and Seismic Data: Analisis Reservoar Migas Non-Konvensional Menggunakan Data Well Logging, Geokimia, dan Seismik - Rahmat Catur Wibowo; Aryka Claudia Eka Putri; Ordas Dewanto (JURNAL GEOCELEBES, 2023)
Since conventional oil and gas is under a depletion phase, unconventional oil, and gas have become prime candidates for current and future oil and gas production. Based on this, investment and research have increased significantly related to unconventional oil and gas exploitation, especially in the North East Java Basin, one of the sedimentary basins producing oil and gas. The research was conducted in the form of well-logging, geochemical, and seismic data analysis to determine the quality and quantity of oil and gas reservoirs. The thickness and TOC value of the reservoir were determined using well-logging data using the Passey method, resulting in a thickness ranging from 900-954 ft and an average TOC value of 3.87 Wt% in the Kujung III Formation. Based on geochemical data analysis, the reservoir has type II kerogen with an immature-early mature maturity level (Ro and Tmax). Meanwhile, based on seismic data, the reservoir thickens to the northwest, ranging from 500-600 m. Unconventional oil and gas reservoirs in the research area have the potential to be developed because they meet several criteria, such as being rich in organic material and thick, even though the maturity level is still in the immature phase. It is estimated that deeper areas will produce different levels of maturity as pressure and temperature increase.